A Quasi Experimental Comparison of TikTok and Instagram Reels as Short Video Microlearning to Improve Cognitive Economics Learning Outcomes - Ni’matul Istiqomah; Siti Mastura Baharudin; Myzan Binti Noor; Nurul Najiha; Ermita Yusida (Global Educational Research Review, 2025)
Purpose – This study assessed and compared the effectiveness of TikTok-based short videos and Instagram Reels as microlearning media to improve cognitive learning outcomes in economics on the APBN and APBD material for Grade XI social science students at SMA Panjura Malang. Methods/Design/Approach – The study used a quasi-experimental method with a pretest-posttest nonequivalent multiple group design. The sample was selected purposively: experimental class 1 used TikTok (n = 25) and experimental class 2 used Instagram Reels (n = 21). The instrument was a 20-item valid (r calculated > r table at the 5% level) and reliable (Cronbach’s Alpha = 0.910) multiple-choice test. Data analysis included the Kolmogorov-Smirnov normality test, Levene’s homogeneity test, the independent sample t-test, and N-gain calculation. Findings – The pretest means were relatively comparable (TikTok = 63.40; Reels = 59.05). After treatment, the posttest means increased with a clear difference (TikTok = 90.20; Reels = 80.95). The t-test showed a significant difference (t = 4.812; df = 44; p < 0.001) with a mean difference of 9.248 and a 95% confidence interval of 5.374 to 13.121. The average N-gain values were 73.53% for TikTok (moderately effective) and 51.93% for Reels (less effective). Originality/Value – This study provides quasi-experimental comparative evidence regarding the effectiveness of two popular short-video platforms for economics learning on APBN and APBD material at the secondary school level. Practical Implications – Economics teachers can prioritize TikTok as a microlearning medium for broad material that requires conceptual understanding, and use Instagram Reels for reinforcement or sharing references with more concise content design given the more limited duration. Keywords TikTok, Instagram Reels, microlearning, cognitive learning outcomes, economics learning Paper type Research paper